Epidemiology of Atrial Fibrillation and Related Myocardial Ischemia or Arrhythmia Events in Chinese Community Population in 2019 - Li, Cheng; Wang, Haicheng; Li, Mohan; Qiu, Xiangjun; Wang, Qunshan; Sun, Jian; Yang, Mei; Feng, Xiangfei; Meng, Shu; Zhang, Pengpai; Liu, Bo; Li, Wei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Atrial fibrillation (AF) is the most common arrhythmia, and the incidence increases rapidly all over the world. The global prevalence of AF (age-adjusted) is 0.60% for men and 0.37% for women and the prevalence of AF in China is 0.65%. It is expected that the number of patients with AF will continue to rise in the future worldwide due to population aging. Objective To explore the prevalence of AF in Chinese community population in 2019 and clarify the prevalence of AF complicated with other arrhythmias and myocardial ischemia (MI) events. Methods The remote electrocardiogram (ECG) diagnosis system of Xinhua Hospital was assessed to the screen participants with ECG evidence of AF between January 1 and December 31, 2019. The prevalence rates of AF and its association with other arrhythmias and MI events were analyzed and subgroup analysis was performed between different sexes and age groups. Results A total of 22,016 AF cases were identified out of all ECGs derived from the remote ECG diagnosis system in 2019. It is estimated that AF was presented in nearly 10.15 million people in China (age-adjusted standardized rate 0.72%, 95% CI 0.20–1.25%) in 2019 and 62% of the AF cases (6.27 million) affected people aged 65 years and above (age-adjusted standardized rate 3.56%, 95% CI 3.28–3.85%). The prevalence rate of AF in males was higher than that in females (p < 0.001), and the ventricular rate of AF patients was faster in females (p < 0.001) and younger patients (p < 0.001). AF patients with lower ventricular rate (under 60 beats per min) were associated with increased prevalence of ventricular escape/escape rhythm [p < 0.001, odds ratio (OR) 5.14] and third-degree atrioventricular block (p < 0.001, OR 32.05). Conclusion The prevalence of AF is higher in the Chinese community population than that was previously reported. AF patients complicated with ECG patterns suggesting myocardial infarction is common in men, and stricter measures should be taken to control the common risk factors of AF and coronary heart disease. It is also important that more attention should be paid to recognize fatal arrhythmias, especially in elderly male patients with AF.